QCM-based immunosensor for rapid detection of Salmonella Typhimurium in food. Issue 1 (December 2018) - Fulgione, Andrea; Cimafonte, Martina; Della Ventura, Bartolomeo; Iannaccone, Marco; Ambrosino, Concetta; Capuano, Federico; Proroga, Yolande; Velotta, Raffaele; Capparelli, Rosanna
Abstract Salmonella Typhimurium is one of the main causes of outbreaks and sporadic cases of human gastroenteritis. At present, the rapid detection of this pathogen is a major goal of biosensing technology applied to food safety. In fact, ISO standardized culture method takes up to ten days to provide a reliable response. In this paper, we describe a relatively simple protocol for detectingSalmonella Typhimurium in chicken meat based on a Quartz-Crystal Microbalance (QCM), which leads to a limit of detection (LOD) less than of 10° CFU/mL and requires a pre-enrichment step lasting only 2 h at 37 °C. The reliability of the proposed immunosensor has been demonstrated through the validation of the experimental results with ISO standardized culture method. The cost-effectiveness of the procedure and the rapidity of the QCM-based biosensor in providing the qualitative response make the analytical method described here suitable for applications in food inspection laboratory and throughout the chain production of food industry.